Heliconia Bug Leptoscelis tricolor Westwood - Christine W. Miller (EDIS)
Though not found in Florida, this insect has been used to examine insect behavior, sexual selection, plant-insect interactions, and color variation. Learn more in this 4-page fact sheet was written by Christine W. Miller and published by the UF Department of Entomology and Nematology, December 2011.